IMPROVING THE FUNCTIONING OF INNOVATIONS OF BANKING RETAIL IN UKRAINE EXAMPLE OF EXTERNAL EXPERIENCE - Демченко, Андрій (Socio-economic relations in the digital society, 2019)
At the current stage in the fi nancial market, in the field of banking marketing and sales of both Ukraine and foreign countries, there is a real revolution associated with the development and implementation of promising innovations. It is estimated that retail banks that are capable of implementing an innovative customer service strategy can increase their operations per client by 50—100 %. Consequently, we propose to consider the development of innovative strategies of implementation policy in the fi nancial market, as well as the possibility of introducing foreign experience in the implementation policy of Ukrainian banks.
Keywords: retail; innovations; marketing policy; financial market; foreign countries; innovative strategies; profitability of banking operations